Genotoxicity in two bivalve species from a coastal lagoon in the south of Portugal - Catarina Almeida, Ana (2020)
DNA damage was evaluated by comet assay in the haemolymph of two bivalve species Ruditapes decussatus and Mytilus galloprovincialis from the Ria Formosa lagoon (south Coast of Portugal). Clams and mussels were sampled from sites close to each other to determine interspecific responses to similar environmental conditions, considering also seasonal and gender differences. Coupled with genotoxic effect, another damage biomarker (lipid peroxidation) was analysed to verify if the conditions that instigate DNA damage can be related with injury to cell membranes. For both species, DNA damage was low, reflecting the low levels of genotoxic contaminants in the lagoon, and no interspecific differences were found. However, seasonal differences were established for both bivalve species, reflecting higher environmental stress in summer. Regarding gender susceptibility, only clams showed differences in percentage of Tail DNA, with females more sensitive to DNA damage than males. Additionally, results for clams point out that factors responsible for LPO may not be the same as those causing genotoxicity. This study demonstrated that DNA damage is a sensitive biomarker to discriminate spatial, temporal and gender differences, being an appropriate biomarker for genotoxicity evaluation even in places of low contamination, such as the Ria Formosa lagoon.